2015
DOI: 10.1515/pjvs-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VPAC1 receptor at the level of mRNA and protein in the porcine female reproductive system

Abstract: The presence and distribution of vasoactive intestinal polypeptide (VIP) receptor VPAC1 was studied in the ovary, oviduct and uterus (uterine horn and cervix) of the domestic pig using methods of molecular biology (RT-PCR and immunoblot) and immunohistochemistry.The expression of VPAC1 receptor at mRNA level was confirmed with RT-PCR in all the studied parts of the porcine female reproductive system by the presence of 525 bp PCR product and at the level of proteins by the detection of 46 kDa protein band in im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Researchers previously found that VIPR1 was involved in the regulation of reproductive activity in chicken (Zhou et al 2008). Recently, Bukowski and Wasowicz (2015) also reported the expression of VIPR1 in porcine female reproductive tissues (such as the uterus, oviduct and ovary). In our present study, VIPR1 showed upregulated expression in the AWGp pituitary gland, which implies that it has a promoting effect on reproductive activities in goat.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers previously found that VIPR1 was involved in the regulation of reproductive activity in chicken (Zhou et al 2008). Recently, Bukowski and Wasowicz (2015) also reported the expression of VIPR1 in porcine female reproductive tissues (such as the uterus, oviduct and ovary). In our present study, VIPR1 showed upregulated expression in the AWGp pituitary gland, which implies that it has a promoting effect on reproductive activities in goat.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of VIP is increased during luteinizing hormone surge in granular cells and follicular fluid. The mRNA transcripts for VIP receptors were identified in 22-day-old mice ovaries and in ovarian follicles at different developmental stages of pigs, as well as in ovarian extracts of human foetuses and women (Barberi et al 2007, Gabbay-Benziv et al 2012, Bukowski & Wąsowicz 2015). As for the proteins, VPAC1 was identified in follicles, mostly in the oocytes, of all human foetus samples (22 gestational weeks onward) and some samples from women and girls (Gabbay-Benziv et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, VIP was found to be associated with the ovary function (Streiter et al 2016). The mRNA transcripts or protein of VIP and its receptors, VPAC1 and VPAC2, were identified in the ovaries of some mammals (Hulshof et al 1994, Barberi et al 2007, Gabbay-Benziv et al 2012, Bukowski & Wąsowicz 2015). Many studies have since showed that VIP might influence the development of preantral and antral follicles (George & Ojeda 1987, Mayerhofer et al 1997, Cecconi et al 2004).…”
Section: Introductionmentioning
confidence: 99%